Impact of cyber-physical system vulnerability, telecontrol system availability and islanding on distribution network reliability. (June 2016) - Conti, S.; La Corte, A.; Nicolosi, R.; Rizzo, S.A.
Abstract: The addition of telecontrolled and automated sectionalizers along the distribution network has permitted to speed up fault location procedures to reduce the restoration time. Nowadays, some utility are installing circuit breakers (CBs) along the network to reduce the average number of customers' outages too, but the use of time selectivity strongly limits the number of CBs installed in topological sequence. In Smart Grid perspective, a protection system upgrade towards telecontrolled CBs allowing to overcome this limitation is expected, and, more in general, a transition towards a cyber-physical system (CPS) implementing protection schemes based on telecontrolled switches only. Moreover, Smart Grids should allow to exploit the potential benefit deriving from autonomous microgrids in terms of service continuity. This work presents an analytical formulation to assess the impact of CPS vulnerability and centralized telecontrol system availability on system reliability in networks where islanding is permitted by regulation. The formulation is applied to a realistic case study. The results have shown that islanding effectively reduces the outage duration even when the CPS is very vulnerable. On the other hand, islanding is able to strongly reduce the outage rate too when the CPS security level is high.